2021
DOI: 10.1016/j.jds.2020.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Dental pulp stem cells from human teeth with deep caries displayed an enhanced angiogenesis potential in vitro

Abstract: Background/purpose Dental pulp stem cells can be isolated from human teeth with deep caries (cDPSCs), but their biological characteristics are still unclear. The aim of this study was to investigate the angiogenic potential of cDPSCs and compare them to dental pulp stem cells from human normal teeth (nDPSCs). Materials and methods Cells were isolated from human pulp tissue of normal and infected teeth with deep caries. Basic mesenchymal stem cell (MSC) characterization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 38 publications
2
12
0
3
Order By: Relevance
“…DPSCs are endowed of a great angiogenic and vasculogenic potential [ 36 ]. They contribute to angiogenesis during pulp regeneration by a paracrine effect and facilitate in vitro and in vivo endothelial tubulogenesis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…DPSCs are endowed of a great angiogenic and vasculogenic potential [ 36 ]. They contribute to angiogenesis during pulp regeneration by a paracrine effect and facilitate in vitro and in vivo endothelial tubulogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…Among their pleiotropic functions, DPSCs are able to facilitate in vitro and in vivo endothelial tubulogenesis [ 36 , 37 , 57 , 58 ]. In contrast, MG-dependent glycation impairs angiogenesis and induce endothelial dysfunction [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dental stem cells from carious tissue seem to possess higher proliferative abilities and a different proteomic profile compared to stem cells from healthy tissues [31,32,373,374]. Recently, in a study where CDPSCs and healthy DPSCs were compared, CDPSCs depicted higher expression of VEGF, among other angiogenesis-related factors, including SDF-1 and PDGF [375]. Moreover, Chen and colleagues showed that when cultured in angiogenic induction medium, CDPSCs expressed higher levels of VEGF, PDGF, and SDF-1 [375].…”
Section: Regulators and Enhancers Of Angiogenesis In Dental Stem Cellsmentioning
confidence: 99%
“…Recently, in a study where CDPSCs and healthy DPSCs were compared, CDPSCs depicted higher expression of VEGF, among other angiogenesis-related factors, including SDF-1 and PDGF [375]. Moreover, Chen and colleagues showed that when cultured in angiogenic induction medium, CDPSCs expressed higher levels of VEGF, PDGF, and SDF-1 [375]. In a tube formation assay, the induced CDPSCs were also able to form vascular-like networks.…”
Section: Regulators and Enhancers Of Angiogenesis In Dental Stem Cellsmentioning
confidence: 99%
“…Recent study from Aksel et al showed that in vitro delivery of VEGF and BMP 2 significantly enhanced the angiogenic and odontogenic potential of human dental pulp stem cells [4]. Noteworthy, the alteration in expression of VEGF and BMP 2 has been identified within human dental pulp cells in inflammation [5,6] as well as in human diabetic pulp tissue [7].…”
Section: Introductionmentioning
confidence: 99%